Brain deep medullary veins on 3-T MRI in a population-based cohort. Issue 3 (March 2021) - Ao, Dong-Hui; Zhang, Ding-Ding; Zhai, Fei-Fei; Zhang, Jiang-Tao; Han, Fei; Li, Ming-Li; Ni, Jun; Yao, Ming; Zhang, Shu-Yang; Cui, Li-Ying; Jin, Zheng-Yu; Zhou, Li-Xin; et al.
Our aim is to investigate whether vascular risk factors are associated with cerebral deep medullary veins (DMVs) and whether DMVs are associated with MRI markers of cerebral small vessel disease (CSVD) or risk of stroke. In a community-based cohort of 1056 participants (mean age 55.7 years), DMVs were identified on susceptibility-weighted imaging (SWI) and counted in periventricular regions. Neuroimaging markers including lacunes, whiter matter hyperintensity (WMH), microbleeds, enlarged perivascular space, and brain atrophy were evaluated. The number of DMVs decreased with age (p = 0.007). After adjusting for age and sex, the number of DMVs was not associated with traditional vascular risk factors. Fewer DMVs was associated with increase of WMH and lacunes, but the association vanished after adjustment for vascular risk factors. However, fewer DMVs were independently associated with brain atrophy (p < 0.001). DMVs were not associated with three-year risk of stroke. Our results suggest that DMV is significantly different from other MRI markers of CSVD regarding risk factors, association with other CSVD markers, and risk of stroke. Nonetheless, the significant association between DMV and brain atrophy suggested the potential role of venules in age-related neurodegenerative process, which deserves further investigation.